Obecności. Prolegomena do tematu o zagranicznej recepcji literatury polskiej - Cudak, Romuald (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Artykuł podejmuje problematykę obecności literatury polskiej w świecie. Wskazuje, że światowość literatury polskiej można rozumieć jako jej udział w światowym systemie literatury, jako obecność literatury światowej w literaturze polskiej oraz jako jej tworzenie poza granicami kraju. Zagadnienia te podejmują badania nad szeroko rozumianą recepcją, badania z zakresu komparatystyki i translatologii oraz historycznoliterackie. W artykule wskazuje się, iż w badaniach pomocne są rozważania teoretyczne m.in. nad procesem i aparatem literatury (R. Escarpit), dotyczące literatury jako polisystemu (I. Even-Zohar) i światowej republiki literatury (P. Casanova) oraz figurami literatury światowej. W drugiej części opisane są przykłady recepcji literatury polskiej w zagranicznych kulturach i polisystemach literackich reprezentatywne dla recepcji hegemona i obecności w systemach peryferyjnych, jak również formy obecności dzieł i pisarzy polskich w świecie (poezja współczesna, twórczość O. Tokarczuk).

The article deals with the issue of the presence of Polish literature around the world. It indicates that the worldliness of Polish literature can be understood as its participation in the global system of literature, as the presence of world literature in Polish literature and as its creation abroad. These issues encompass research on broadly-defined reception, research in the scope of comparative literature studies and translation studies as well as historical and literary research. The article also points out that research is helped by theoretical discussions, among others, on the literary process and apparatus (R. Escarpit), on literature as a polysystem (I. Even-Zohar), on the world republic of letters (P. Casanova) and on the figures of world literature. The second part describes examples of reception of Polish literature in foreign cultures and literary polysystems representative of reception of the hegemon and the presence in peripheral systems, as well as forms of presence of Polish works and authors around the world (contemporary poetry, the works of O. Tokarczuk).
Presences. Prolegomena to the topic of foreign reception of Polish literature
Keywords: recepcja literacka; recepcja literatury polskiej w świecie; literatura polska; Polish literature; literary reception; reception of Polish literature around the world